2004
DOI: 10.1002/cncr.20018
|View full text |Cite
|
Sign up to set email alerts
|

Reduced folate carrier mutations are not the mechanism underlying methotrexate resistance in childhood acute lymphoblastic leukemia

Abstract: BACKGROUND Although the majority of children with acute lymphoblastic leukemia (ALL) are cured with combination chemotherapy containing methotrexate (MTX), drug resistance contributes to treatment failure for a substantial fraction of patients. The primary transporter for folates and MTX is the reduced folate carrier (RFC). Impaired drug transport is a documented mechanism of MTX resistance in patients with ALL; however, to the authors' knowledge it is not known whether inactivating RFC mutations are a contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 38 publications
5
22
0
Order By: Relevance
“…Our results showed a decreased expression of RFC mRNA in drug-induced cells. In primary cells, RFC mRNA is significantly higher than that of the inducible cell line, and this is consistent with the literature (Guo et al, 1999;Hattinger et al, 2003, Ifergan et al, 2003Kaufman et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed a decreased expression of RFC mRNA in drug-induced cells. In primary cells, RFC mRNA is significantly higher than that of the inducible cell line, and this is consistent with the literature (Guo et al, 1999;Hattinger et al, 2003, Ifergan et al, 2003Kaufman et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, Kaufman et al (2004) found that in a child with acute lymphoblastic tumor, the mutations of genes are not a potential cause of MTX resistance. Guo et al (1999) analyzed RFC and DHFR mRNA in 42 cases (primary and metastatic osteosarcoma specimens) by semi-quantitative RT-PCR and found the mechanism of osteosarcoma chemotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The remaining discussion is restricted to FRa, the most widely studied FR isoform. The transport kinetics and affinity for folates and antifolates differ significantly between systems (Table I), in part, because FRa does not bind and carry folate into the cell as does RFC, but binds and internalizes folate via endocytosis.…”
Section: Folate Receptor Vs Reduced Folate Carrier Transportmentioning
confidence: 99%
“…22 It is a ubiquitous resident of most cells, and mediates the uptake of reduced folates and methotrexate with relatively high affinity and at higher, micromolar concentrations (K m : 1-10 lM); it has relatively poor affinity for oxidized folic acid (K m : 200-400 lM). 21,27,28 The potential binding capacity of the RFC for reduced folates is several hundred times greater than the amount of folate in serum.…”
Section: Folate Receptor Vs Reduced Folate Carrier Transportmentioning
confidence: 99%
“…Consistently, alternative phosphorylations also have been reported to render Sp1 a transcriptional repressor. 29,30 An important mechanism of antifolate resistance in ALL 31 and other malignancies 32 is impaired antifolate transport due to loss of RFC function, 2,33 resulting from mutational inactivation 34 and/or transcriptional silencing. [9][10][11] This loss of function, as we have recently shown in multiple antifolate-resistant human leukemia cell lines with defective antifolate uptake, is due either to mutations in the RFC gene 34 or decreased RFC mRNA levels caused by a methylation-independent transcriptional silencing of the RFC gene.…”
Section: Introductionmentioning
confidence: 99%